Decolorization and Bioelectricity Generation from Palm Oil Mill Effluent by a Photosynthetic Bacterial Consortium - Pimprapa Chaijak; Alisa Kongthong (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Palm oil mill effluent (POME) is the dark brown agricultural wastewater from palm oil extraction factories. It is difficult to decolorize using conventional methods. Melanoidin is a dark-colored polymer formed through the Maillard reaction which is the primary cause of the dark color in POME. This study investigated the potential of a photosynthetic bacterial consortium consisting of Blastochloris sulfoviridis and Lentimicrobium saccharophilum for POME treatment and bioenergy generation. The consortium effectively removed melanoidin content (68.89±0.84%) and color (60.87±1.22%) from POME without the addition of chemicals or culture medium. Additionally, a microbial fuel cell (MFC) integrated with the consortium generated apower output of up to 5.70±1.06 W m-3. The degraded metabolites were analyzed by gas chromatography-mass spectrometry (GC-MS) after treatment. The results revealed that melanoidin was converted to 1-ethyl-2-methylbenzene, 1,2,4-trimethylbenzene, decamethylcyclopentasiloxane, dodecamethylcyclohexane, butylated hydroxytoluene, and stigmasta-3,5-diene. Following treatment, the cell pellet was recovered and analyzed for valuable by-products. Carotenoid and astaxanthin pigments were extracted with yields of 0.32±0.01 and 0.02±0.00 mg g-1, respectively. These findings demonstrate the versatility of the photosynthetic bacterial consortium, which offers a sustainable solution for POME treatment while simultaneously POME decolorization and producing bioenergy and valuable compounds.